Effect of international working experience of individual auditors on audit quality: Evidence from China. (29th May 2017) - Chen, Xiaolin; Dai, Yunhao; Kong, Dongmin; Tan, Weiqiang
Abstract: This paper investigates the effects of auditors with international working experience on audit quality in emerging markets. Such auditors are associated with better audit quality, a pattern that is further supported by an examination based on a propensity score matching sample that controls for endogeneity. Chief financial officers with international experience are more conservative in the client company of their auditors who have international working experience. Further, reviewer partners with international working experience provide better audit quality in terms of low accruals, less below‐the‐line items, and less audit reporting aggressiveness, while engagement partners with international working experience require high audit fees. Moreover, financial reports signed by auditors with international working experience significantly increase analyst forecast accuracy and decrease analyst forecast dispersion. Our results are robust to different specifications and alternative measures. Overall, this paper highlights the importance of human capital and provides direct evidence on how auditors with international working experience use their knowledge and audit skills in emerging markets.